Screening potential diagnostic biomarkers for PLA2R‑associated idiopathic membranous nephropathy by WGCNA analysis and LASSO algorithm - Jinxu Huang; Yaqing Huang; Xiaoling Zeng; Yuhong Zhang; Junneng Zhang; Qingchu Hong; Yongtiao Peng (Renal Failure)
Adult nephrotic syndrome is primarily caused by membranous nephropathy (MN), with idiopathic membranous nephropathy (IMN) being a prominent subtype. The onset of phospholipase A2 receptor (PLA2R1)-associated IMN is critically linked to M-type PLA2R1 exposure, yet the mechanism underlying glomerular injury remains unclear. In this study, membranous nephropathy datasets (GSE115857, GSE200828) were retrieved from GEO. Differential gene expression was analyzed using the ‘limma’ R package. WGCNA filtered PLA2R-related modules and intersected genes. LASSO regression, evaluated by ROC analysis, identified characteristic genes. Binomial logistic regression assessed their association with IMN. Validation was performed in the GSE133288 dataset. IHC and qRT-PCR detected characteristic gene expression in PLA2R-positive patients. This study identified elevated PLA2R expression in IMN patients among 117 DEGs. PPI analysis suggested enrichment in Golgi membranes, co-regulation, and glucocorticoid responsiveness, implicating the PPAR pathway by KEGG. WGCNA revealed a 440-gene brown module associated with IMN-PLA2R, with ECM1, SLC19A2, RASD1, FOSB, KDELR3, ZFP36, and ELF4 highlighted as diagnostic markers by ROC analysis. Clinical validation confirmed ECM1 upregulation increased IMN risk, while upregulation of SLC19A2, ZFP36, RASD1, and FOSB decreased it. ECM1 positively correlated with PLA2R, whereas SLC19A2, ZFP36, and FOSB negatively correlated. IHC analysis demonstrated consistent gene expression patterns in IMN tissues, with podocyte exposure to PLA2R-positive serum reducing viability and increasing apoptosis. Functional studies, prompted by RASD1 downregulation, revealed enhanced cell activity and reduced apoptosis upon RASD1 overexpression compared to the Serum + Ov-NC control. Collectively, this study identified diagnostic markers for PLA2R-related IMN, offering novel therapeutic targets for the treatment of IMN.